Dealing with work overload in the IT industry - Mosquera, Pilar; Soares, Maria Eduarda (Management decision, 2024)
PurposeWork overload has become a relevant issue in the Information Technology (IT) industry, with negative effects for individuals and organizations alike. This study aims to analyse the role of personal resources in a broad model regarding the effects of work overload on performance and well-being for the particular case of IT professionals. Considering the specificities of the IT industry, three personal resources were included in this study: one stable personality variable (conscientiousness) and two more malleable variables (work-life balance and psychological detachment).Design/methodology/approachTo test the model, the authors use a sample of 144 IT Portuguese professionals. The authors collected data through an online questionnaire shared in social networks and IT social network communities. The authors use partial least squares (PLS) for data analysis.FindingsThe results show that work overload negatively impacts on employees’ life satisfaction, psychological detachment, work-life balance and task performance. Conscientiousness is positively related with two positive outcomes: task performance and life satisfaction. Work-life balance has a mediating effect in the relationship between work overload and life satisfaction.Practical implicationsThese findings emphasize the need to promote conscientiousness in IT professionals, as well as reduce workload and promote family-friendly working environments to foster work-life balance and life satisfaction.Originality/valueBy testing this model, the authors aim to contribute to the current knowledge on the role of personal resources in the Job Demands-Resources model, which is still unclear and under-researched.